(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social Media Marketing is very important and it is among the most successful tool and technique in the field of every type of advertising. It is already known that how various marketing tools and techniques can be increased number of selling articles is the main aim of every businessman. No doubt it can raise the profit of a various companies exponent. The main aim of this study is to examine aimed to examine how social media marketing will affect the final consumer behavior among person who mostly use social media websites and also to find out the forecasted relationships among various social media marketing activities, customer activities and behavior of the consumer. The implementation of Social Media websites is emerging continuously to give the satisfaction of the social needs of websites users, at the mean while time it has also increased the opportunities for corporate to advertised their products and services in a personalized way. The past record shows that social media has contributed significantly in changing the thinking of customers in buying process. Organizations can’t under estimate the growing importance of social Networking sites with reference to consumer behavior and how its effecting to consumer behavior.